Hubungan Pengetahuan dan Sikap Remaja dengan Kecemasan Terhadap Perubahan Fisiologis (Pubertas) - Nani Handayani; Siti Sukriawati (Jurnal Obstretika Scientia, 2017)
The aim of the study is to investigate the relationship of knowledge and teenager’s attitude with anxiety over physiological changes (puberty) in class IX students of Junior High School 1 Pamarayan in 2016.The design of the study incorporates cross sectional analytical survey. The population in this study consists of all class IX students of Junior High School 1 Pamarayan who are 193 students.  The sample taken is 130  students. The sample taking was executed by doing simple random sampling. The result shows that the frequency of class IX students who are anxious are 124 students (95.4%), the students whose knowledge aren’t sufficient are 26 students (73.8%), the students who signify negative attitude are 58 students (44.6%). According to bivariate analysis there is no significant relationship between knowledge and anxiety over physiological changes, showing p – value 0.652 (p 0.05) and there is no relationship between students’ attitude and anxiety over physiological changes, showing p- value 0.691 (p 0.05). It is suggested that students need a school program to inform and socialize about teenage health, particularly a counselling about physiological changes.